An Export Model Proposal Based on Integrated SWOT-AHP Methods for Sustainable Naval Shipbuilding Industry with a Real Case Application - Yilmaz, Bilkutay; Yilmaz, Huseyin (OLD CITY PUBLISHING INC, 2024)
Since sustainability is completely critical for industry, this study puts forwards an integrated methodology based on Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis and Analytic Hierarchy Process (AHP) method to propose an export model for sustainable naval shipbuilding industry. This study, which includes real-cases and theoretical work, proposes a systematic approach to create export model for a sustainable naval shipbuilding industry by providing a roadmap for companies together with the external necessities to pursue a to-the-point export strategy. The methodology SWOT analysis is used to determine internal and external factors of the export potential for Turkish naval shipbuilding industry. Then, the AHP method is employed to prioritize the critical criteria and sub-criteria of naval shipbuilding projects in order to create a successful export model. The proposed model has been applied with a real case study to obtain a robust export model. Finally, a sensitivity analysis is also adopted to verify and extend usability of obtained results for soundness of the model. The obtained results of this study disclose that criterion Resources which includes sub criteria such as importance of government-supported credit/incentive mechanisms, presenting the offer with the financial credit package, and the sufficiency of the company's capital, arises as the foremost important criteria for obtaining a successful export project methodology. While the criterion Project Management that includes sub criteria such as ability to deliver in accordance with the project schedule, and the ability to produce timely solutions to additional and unprecedented requirements is also determined as the least favored criteria for reaching an export project model.
Keywords: Sustainability; SWOT analysis; analytical hierarchy process; defense industry; naval shipbuilding industry; export strategies; INNOVATION; CAPABILITIES; STRATEGIES; IMPACT; TRADE; Computer Science; Science & Technology - Other Topics